Photodegradation of methyl orange using copper oxide doped zinc oxide under ultraviolet light irradiation - Jefri, Siti Nur Surhayani (2017)
Copper oxide doped zinc oxide photocatalyst was synthesized by sonochemistry method using Zn(NO3)2.6H2O and Cu(NO3)2.3H2O as precursor and two different precipitation agents NaOH and NH4OH. The precipitate was washed, dried and calcined at 400°C for 3 hr. The product was characterized by X-ray diffractometry (XRD), UV- Vis NIR Spectrophotometer, field emission scanning electron microscopy (FE-SEM), Transmission Electron Microscope (TEM) and surface area (BET method) . XRD result showed the sonicated ZnO produced by NaOH as precipitation agent has bigger crystallite size, 61.1 nm and the surface area was 4.43 nm2/g . After doping with CuO, the crystallite size decreased to 19.4 nm and the surface area increased to 8.2 nm2/g. The band gap energy of ZnO and CuO doped ZnO was 3.3 eV respectively. Majority of the particles were about 13.0 nm as obtained from the particle size distribution histrogram After doping with CuO, the particle size decreased to 10.8 nm. The efficiency of the photocatalyst was examined by photodegrading Methylene Orange (MO). The effects of photodegradation parameters such as photocatalyst mass loading, MO initial concentration and MO initial pH examined. The experiments were evaluated by photodegradation of methyl orange under UV light irradiation for 4 hours. Photocatalytic activities showed that the highest removal was when the 0.6g of 0.8% CuO doped ZnO used in 5ppm MO with pH 6.8 which is the percentage removal was 54.1%. Experimental design methodology also applied using response surface methodology (RSM). The multivariate experimental design was employed to develop a quadratic model as a functional relationship between the mg/g per of MO and three experimental factors (mass loading, MO initial concentration and MO initial pH). The highest removal of MO approached 12.8 mg/g when the 0.2g of 0.8% CuO doped ZnO used in 5ppm MO with pH 5.